Value Creation Analysis: Semiconductor Intellectual Property Business Models and Dynamic Capabilities - Chen, Wei-Ting; Khan, Mohammad Saud; Iftikhar, Rehan (IEEE transactions on engineering management, 2023)
Semiconductor intellectual property (SIP) represents a crucial component of integrated circuit design activities. However, many small SIP firms fail to create value and adopt a viable business model. This article aims to investigate the value creation mechanism within the SIP business by drawing on the business model and dynamic capabilities views of the firm. First, the authors classify the forms and types of SIP from a technology and market perspective. Analyzing ten leading SIP firms, three SIP business models based on resources, competencies, and strategies are then identified. Dynamic capabilities are then linked to the selection and implementation of classified business models. Findings of the study suggest that existing SIP business models primarily favor large vendors. Keystone business model is proposed as a possible successful business model for small vendors. Consequently, this article provides insights and opportunities for leveraging the SIP ecosystem and business model innovation for small firms in the industry.